Development of an Elementary-Level Hanzi Writing Practice Book for Education of Chinese Language Program Semarang State University - Dian Yuni Pamuji; Anggraeni Anggraeni; Ria Riski Marsuki (Universitas Negeri Semarang, 2023)
In language learning, especially Chinese Language, writing is one of the four basic skills students must master. In learning to write, students have to require to master writing Hanzi. Writing Hanzi requires repeated practice and training so that students become accustomed to it and can memorize Hanzi writing. Hanzi writing practice books are really needed as supporting media in learning to write Hanzi. This research aims to produce an elementary-level Hanzi writing practice book as a learning medium for students by 1) Describing the results of analyzing learning media needs in the form of a basic-level Hanzi writing practice book. 2) Describe the results of designing a learning media product in the form of an elementary-level Hanzi writing practice book. 3) Describe the results of expert validation regarding learning media in the form of elementary-level Hanzi writing practice books. The learning media in a writing practice book is adapted to learning material, including Hanzi, pinyin, meaning, number of strokes, order of writing the strokes, and columns for writing practice. The research method used in this research is a research and development method with research stages up to the 5th stage, namely : (a) Potential and Problems, (b) Data Collection, (c) Product Design, (d) Design Validation, and (e) Design Revision. The expert validation results stated that this writing exercise book was suitable for trial use.